Speech Functions and Mood System Realization in the Finalists’ Speeches at Miss Grand International 2020 - Tomy Widiyanto; Hendi Pratama; Rahayu Puji Haryanti (Universitas Negeri Semarang, 2022)
Today, the idea of communication is as diverse as the goals for learning. Speech is one of presentational information in oral format which can be needs to have the 21st century skill. Language of speech distinguishes grammatical moods. The speeches in the top 10 finalists of Miss Grand International 2020 was chosen to analyze the realization of speech functions and mood system. Non-participatory observation, selecting the media and classifying the subject of the research, and literature review were steps to collect the data. Analysis data was interpreted and reported in qualitative procedures. It was illuminated that the finalist of Malaysia mostly showed offer among other finalists. The finalist of Guatemala delivered mostly the command. The finalist of Indonesia was counted as the most produced statement. The questions were produced mostly by the finalist of Malaysia and the finalist of Argentina. The use of declarative mood was mostly made by the finalist of Malaysia. The polar interrogative was turned by the finalist of Argentina. Moreover, the imperative was mostly produced by the finalist of Czech Republic. Thus, the statement of speech functions was congruent with declarative of mood system. Likewise, command showed the congruency of imperative. Implementing speech in the English classroom can build students’ confidence and interest in enhancing their public speaking skill. Furthermore, the research under topic speech in the pageant can help to analyze someone’s culture from the speech pattern, accents, vocabulary, and dialect. By this way, the research was conducted to be beneficial for learning language development.